2017
DOI: 10.1002/ecs2.1916
|View full text |Cite
|
Sign up to set email alerts
|

Immediate signaling flexibility in response to experimental noise in urban, but not rural, white‐crowned sparrows

Abstract: Abstract. Background noise can interfere with acoustic communication. Signal modifications have the potential to increase signal-to-noise ratios and reduce the masking effect of noise. Immediate signaling flexibility, a type of vocal plasticity, allows animals to modify their signal to optimize transmission depending on ambient noise conditions. Results from previous studies provide conflicting evidence about whether expression of immediate signaling flexibility is dependent upon the signaler having prior expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 50 publications
(122 reference statements)
5
28
1
1
Order By: Relevance
“…That is, through experience they may no longer attend to noise stimuli. Recent evidence suggests that modifiability of behaviours against noise can depend on prior experience with noise in birds (Gentry et al., ; LaZerte et al., ). However, although detection and initiation of phonotaxis can occur more quickly in nonoverlapping noise, the masking potential remains for overlapping noise and reductions in distraction due to noise with experience do not help mitigate the problem of failing to orient advertisement calls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, through experience they may no longer attend to noise stimuli. Recent evidence suggests that modifiability of behaviours against noise can depend on prior experience with noise in birds (Gentry et al., ; LaZerte et al., ). However, although detection and initiation of phonotaxis can occur more quickly in nonoverlapping noise, the masking potential remains for overlapping noise and reductions in distraction due to noise with experience do not help mitigate the problem of failing to orient advertisement calls.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is plenty of evidence showing that signallers can reduce negative effects of acoustic masking by modifying their signal properties such as frequencies (Cunnington & Fahrig, ; Francis, Ortega, & Cruz, ; Patricelli & Blickley, ; Slabbekoorn & Peet, ) or amplitudes (i.e., the Lombard effects) (Halfwerk, Lea, Guerra, Page, & Ryan, ; Zollinger & Brumm, ). Moreover, recent studies have shown that prior experience with noise can be related to such modifiability in signallers (Gentry, Derryberry, Danner, Danner, & Luther, ; LaZerte et al., ). Although evidence of signaller responses to noise is quite common (Slabbekoorn, ), behavioural responses of signal receivers has received comparably very little attention (but see Kleist, Guralnick, Cruz, & Francis, ; Luther, Danner, Danner, Gentry, & Derryberry, ) and, to our knowledge, only one study has investigated behavioural plasticity in receivers in response to noise (Halfwerk, Bot, & Slabbekoorn, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note that, in our study on mountain chickadees, had we only used focal males from quiet areas, we would have concluded that mountain chickadees clearly discriminated between Urban and Rural stimuli in experimental noise. This highlights the importance again of considering context and the effect that long-term familiarity with anthropogenic noise may have on free-ranging animals (Gentry et al, 2017;Harding et al, 2018;LaZerte et al, 2016;Nedelec et al, 2016). Finally, we appreciated comments provided by Walt Koenig and two anonymous reviewers that helped us improve the manuscript.…”
Section: Con Clus Ionsmentioning
confidence: 88%
“…This highlights the importance again of considering context and the effect that long-term familiarity with anthropogenic noise may have on free-ranging animals (Gentry et al, 2017;Harding et al, 2018;LaZerte et al, 2016;Nedelec et al, 2016). Further laboratory and field studies of receiver detection and discrimination are needed to help determine whether this is the result of improved perception in noisy habitats by urban receivers or increased aggression in urban habitats, or some combination of the two.…”
Section: Con Clus Ionsmentioning
confidence: 99%
“…The early experience hypothesis argues that the presence of noise during development affects song structure and production later in life. For example, evidence from black-capped chickadees ( Poecile atricapillus ) and white-crowned sparrows ( Zonotrichia leucophrys ) suggests that experiencing noise early in life may be necessary for the development of noise-induced plasticity in song frequency in adulthood [33, 34]. In addition to inducing plasticity, noise during development may mask lower frequency tutor songs and cause selective learning of songs with higher minimum frequencies in urban environments [35].…”
Section: Introductionmentioning
confidence: 99%